Virucidal activity presence in Trichilia glabra leaves - Cella, M. (2004)
Different immunomodulatory activities present in Trichilia glabra (TG) leaf extracts have already been described. Particularly, chloroform-methanol extracts were responsible for an in-vivo anti-inflammatory effect. The effect of such extracts on the infectivity of enveloped and naked viruses were investigated. Methanolic fraction extracts were active against herpes simplex virus type 1 (HSV-1) and vesicular stomatitis virus (VSV), while no activity against poliovirus type 3 was observed. VSV was slightly more affected than HSV-1: 2.8 log10 reduction in VSV titer against 2.4 log10 reduction in HSV-1 titer when 0.25 mg/ml F2 fraction was tested and a reduction of 2.7 log10 in VSV virus titer and of 1.5 log10 in HSV-1 virus titer was observed when 0.25 mg/ml F3 fraction was tested. Results obtained in this work suggest a potential pharmaceutical use of TG extract components.